Igniting students' inner determination: the role of a need-supportive climate. Issue 4 (2nd July 2018) - Adams, Curt; Khojasteh, Jam
Abstract : Purpose: Self-determination theory was used to conceptualize a type of school climate that has consequences for the social, emotional and cognitive well-being of students. The purpose of this paper is to argue that a need-supportive climate emerges through a general pattern of interactions that students experience as supporting their psychological needs. Design/methodology/approach: A hypothesized model was tested whereby the latent need-supportive climate variable was predicted to work through identification with school to influence student grit. Ex post facto data were collected during the 2015–2016 school year from a random sample of students in either the 5th, 8th, or 11th grades in 71 schools located in a southwestern city in the USA. A total of 3, 233 students received surveys. Of these students, the authors received useable responses from 2, 587 students for a response rate of 80 percent. Findings: Findings support the hypothesis that autonomy-support, competence-support and relational-support are integrated and combine to shape experiences that align with student psychological needs. Additionally, students who experienced a need-supportive climate were also more likely to identify with school and expressed higher grit toward academic pursuits. Originality/value: A need-supportive climate adds meaning to more general characterizations of school life (e.g. healthy, supportive, open, etc.) and it affords a theoretically derived explanation for how the social side of schools nurtures the inner determination of students to excel.